Convergence to fair wage growth? Evidence from European countries on the link between productivity and real compensation growth, 1970-2017 - Sotiria Theodoropoulou (European Trade Union Institute (ETUI), 2019)
This paper examines two questions. First, whether and if so, to what extent real compensation growth has been systematically associated with labour productivity growth in the past five decades, once other factors determining real compensation growth have been taken into account. And secondly, whether the apparent gap between real compensation and productivity growth, which can also be considered to be a measure of 'fair' wage growth, has been growing or diminishing over time and whether the EU member states have been converging to or diverging from it. The first question has been the subject of recently renewed policy and academic interest, especially in the United States, but also in Europe. Answering this question has important implications regarding the policies that are necessary (but not necessarily sufficient) to support stronger real wage growth, which could help to reduce income inequality and support currently globally disappointing output growth rates. The particular contribution of this paper is that it builds on the existing empirical literature to provide country-specific evidence on 25 EU member states on the first question and examines this evidence from the perspective of the European Pillar of Social Rights. It highlights the diversity in the degrees to which various EU member states have been experiencing 'fair' wage growth and thus provides some insights towards understanding what needs to be done in order to pursue this aim. The analysis in this paper suggests that the linkage between productivity and real compensation growth is still present in most of the countries examined, but that in most of them workers have not been reaping the full gains from productivity growth. The second question is pertinent to the implementation of the 'fair wages' principle of the European Pillar of Social Rights. This paper provides evidence suggesting that following the period of 1970-1994 when the gap between productivity and real compensation growth widened on average, there has been convergence towards a 'fair' wage growth pattern since the mid-1990s, which nevertheless did not reverse the earlier losses.
Keywords: 330; wage level; productivity development; EU countries; Lohnniveau; Produktivitätsentwicklung; EU-Staaten